An overview of online marketing promotion activities in the event tourism of the Moravica district - Papić, Miloš; Garabinović, Dušan; Blagojević, Marija (Hotel and Tourism Management, 2018)
The development of technology in the last few decades has led to major changes in almost all areas of the economy. This is mostly related to production and service delivery processes, but also to other accompanying activities, without which the functioning of business systems is unthinkable today. The Internet is probably one of the most important representatives of this development and a factor without which the modern world can hardly be imagined. Its role is also highlighted in the field of marketing with the emergence of a new concept known as Internet marketing. By linking online marketing and manifestations/events, as one of the most important factors in tourism activity, the basis for satisfying the demands that modern age implies in the process of achieving quality relationships with the target market is created. Events and the way of their presentation, as the basis of marketing communications, with their specificities contribute to the uniqueness of a particular area by creating its image. The aim of this paper was to analyze the degree of the use of the Internet in the marketing activities of local tourist organizations as well as the tourist events of the Moravica administrative district, with particular reference to the use of websites and four most popular social networks.